Factors influence construction time performance for IBS in Malaysia Construction Industry [electronic resource] - Siti Nur Hafizeanie Salahuddin, 1980-; Fakulti Kejuruteraan Awam (2010)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2010